Studi Formulasi Massage Oil Aromaterapi dari Lavender, Citronella dan Chamomile dengan Kombinasi Olive Oil, Almond Oil, dan Virgin Coconut Oil sebagai Carrier Oil - Nur Ermawati; Alya Rahma Oktaviana (Lembaga Pengembangan Kinerja Dosen, 2026)
The cosmetic industry continues to grow rapidly along with the increasing demand for natural-based body care products, one of which is massage oil. Essential oils such as lavender, citronella, and chamomile are known to have synergistic effects as relaxation agents, anxiety reducers, and anti-inflammatory agents. To support the safety and effectiveness of their use, the selection of appropriate carrier oils, such as olive oil, almond oil, and virgin coconut oil (VCO), is required due to their good penetration ability and moisturizing properties. This study aimed to determine the effect of variations in carrier oils on the physical and sensory characteristics of aromatherapy massage oil preparations and to identify the most optimal formulation. The research was conducted experimentally by formulating three massage oil formulations using a combination of lavender, citronella, and chamomile essential oils with different carrier oil compositions. The evaluations included organoleptic tests, pH, viscosity, specific gravity, stability, irritation tests, and hedonic tests. The results showed that all formulations were liquid, homogeneous, stable for 28 days, had pH values within the normal skin pH range, met the required viscosity and specific gravity standards, and did not cause skin irritation. Based on the hedonic test, formulation F2 was the most preferred by respondents and was determined to be the best formulation due to its most favorable aroma, texture, and comfort during use. Therefore, variations in carrier oils influence the characteristics of massage oil preparations and enable the determination of the optimal formulation